Entrevista con Charles Portilla Revollar - Ronald Delgado Morales; Bianca López Bobbio; Luisa Mazeyra Zúñiga; Lizbeth Medina Zeballos; Sol Ojeda Cama; Rodrigo Quispe Gutiérrez; Rosmery Taya Huamaní (Revista de Psicología, 2020)
Charles Portilla Revollar